2018
DOI: 10.3390/ijms19092663
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D: Effect on Haematopoiesis and Immune System and Clinical Applications

Abstract: Vitamin D is a steroid-like hormone which acts by binding to vitamin D receptor (VDR). It plays a main role in the calcium homeostasis and metabolism. In addition, vitamin D display other important effects called “non-classical actions.” Among them, vitamin D regulates immune cells function and hematopoietic cells differentiation and proliferation. Based on these effects, it is currently being evaluated for the treatment of hematologic malignancies. In addition, vitamin D levels have been correlated with patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 184 publications
(210 reference statements)
5
107
1
9
Order By: Relevance
“…These results are in line with previous findings by Park and colleagues, that showed an inverse association between 25(OH)D levels and platelet indices in the general adult population but did not investigate possible differences between healthy and unhealthy subjects [19]. To better explain the interrelationship between obesity, vitamin D, platelet count and cardiovascular risk, it is of note that vitamin D has a direct role in regulating hematopoietic cells' differentiation [21]. Moreover, a previous study [22] showed that vitamin D receptors modulate megakaryocytopoiesis and platelet activation, which are calcium-dependent events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with previous findings by Park and colleagues, that showed an inverse association between 25(OH)D levels and platelet indices in the general adult population but did not investigate possible differences between healthy and unhealthy subjects [19]. To better explain the interrelationship between obesity, vitamin D, platelet count and cardiovascular risk, it is of note that vitamin D has a direct role in regulating hematopoietic cells' differentiation [21]. Moreover, a previous study [22] showed that vitamin D receptors modulate megakaryocytopoiesis and platelet activation, which are calcium-dependent events.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, a physiological anti-thrombogenic and anti-inflammatory activity of vitamin D has also been reported [23,24]. Therefore, we believe that the consequence of events is that obesity is responsible for a decrease of vitamin D circulating concentrations [6], lower vitamin D levels are responsible for higher platelet number [21,22] and, finally, obesity is indirectly responsible for higher platelet count, thus higher cardiovascular risk.…”
Section: Discussionmentioning
confidence: 82%
“…Vitamin D interacts directly with DCs to inhibit their migration, differentiation and maturation, promoting a tolerogenic T cell response [26‐27,42,43] by the induction of T reg cells and the release of high amounts of anti‐inflammatory cytokines [28,44]. Most studies that have explored the immunomodulatory effects of vitamin D in vitro have focused on the use of 1,25(OH) 2 D 3 or synthetic analogues [45]. Interestingly, it has been demonstrated that macrophages and DCs are also capable of responding to 25OHD [45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect of vitamin D is currently under investigation in MS patients who frequently display decreased vitamin D levels [179]. Vitamin D supplementation seems to reduce neuronal damage after oxidative stress in cell culture [180] and has also been investigated regarding its impact on immune cells [181]. While vitamin D supplementation and subsequent hypercalcemia was counterproductive in EAE mice, a lower concentration seemed to be slightly beneficial [182].…”
Section: Calcium and Immune Cell Activationmentioning
confidence: 99%